1991
DOI: 10.1128/jb.173.2.768-775.1991
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of the gene for outer membrane protein OprF in the family Pseudomonadaceae: sequence of the Pseudomonas syringae oprF gene

Abstract: The conservation of the oprF gene for the major outer membrane protein OprF was determined by restriction mapping and Southern blot hybridization with the Pseudomonas aeruginosa oprF gene as a probe. The restriction map was highly conserved among 16 of the 17 serotype type strains and 42 clinical isolates of P. aeruginosa. Only the serotype 12 isolate and one clinical isolate showed small differences in restriction pattern. Southern probing of PstI chromosomal digests of 14 species from the family Pseudomonada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0

Year Published

1992
1992
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 36 publications
4
26
0
Order By: Relevance
“…This is not unexpected since earlier reports based on cross-reactivity of antibodies (Mutharia & Hancock, 1985) and on DNA hybridization (Ullstrom et al, 1991) indicated the occurrence of oprF-like genes and their products in several species of this group. OprF as a reference, only residues differing in the other proteins are shown.…”
Section: Pcr Amplification and Sequencing Of Oprf Genesmentioning
confidence: 74%
See 1 more Smart Citation
“…This is not unexpected since earlier reports based on cross-reactivity of antibodies (Mutharia & Hancock, 1985) and on DNA hybridization (Ullstrom et al, 1991) indicated the occurrence of oprF-like genes and their products in several species of this group. OprF as a reference, only residues differing in the other proteins are shown.…”
Section: Pcr Amplification and Sequencing Of Oprf Genesmentioning
confidence: 74%
“…Fig. 3 shows that the signal peptides of the different OprF proteins were highly similar and strongly resembled the corresponding part of the unprocessed OprF from P. syringae (Ullstrom et al, 1991). For the mature OprFs, the seven sequences showed 83.3 YO identity over 275 residues, and 27 of the 46 non-conserved residues contained at least one substitution with a dissimilar residue.…”
Section: Pcr Amplification and Sequencing Of Oprf Genesmentioning
confidence: 93%
“…syringae 61 hrplhrm genes were expressed in E. coli at a level below the sensitivity of the assay, similar analyses were performed comparing the wild-type strain with one of the P. syringae pv. syringae 61 (24) have shown that inactivation of a single hrp gene is sufficient to block production of the HR-eliciting factor or activity. As before, no specific epitopes were associated with expression of the hrplhrm genes.…”
Section: Resultsmentioning
confidence: 99%
“…Cell collapse was evident within 18 h in leaf tissue infiltrated with P. syringae pv. syringae 61 and E. coli MC4100(pHIR11).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation